Multifunctional 5-hydroxyconiferaldehyde O-methyltransferases (CAldOMTs) in plant metabolism - Lam, Lydia Pui Ying (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.